Evaluation of civil flight deck design using fuzzy logic approach - Aminian, Negin O.; Romli, Fairuz Izzuddin; Salim, Salim M. (Engg Journals Publications, 2017)
A good ergonomic design for cockpit can greatly help to improve pilots’ task efficiency and reduce potential human errors, hence increasing safety of flight operations. The ergonomics aspect should be more emphasized nowadays as the cockpit system moves towards more flight automation, particularly regarding the human-machine interactions. In this study, the main objective is to highlight whether there is potential improvement for current cockpit system design. The evaluation process is done using fuzzy logic pattern recognition approach and three evaluation objects have been chosen, which are instrument panel, pedestal panel and pilot's seat. 14 experts are involved in evaluating these objects through a survey that has been distributed to them. 10 evaluation criteria are established for the study and cockpit designs of two existing aircraft series are used in the example case study. All in all, the results highlight that there exists some rooms for improvement for the current cockpit design that should be considered in the future to enhance its efficiency.